2005
DOI: 10.1245/aso.2005.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Transcription Factors Snail, Slug, and Twist and Their Clinical Significance in Human Breast Cancer

Abstract: These data demonstrate that all three transcription factors have inappropriate expression in breast cancer and that this may play a part in the progression of human breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
320
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(341 citation statements)
references
References 35 publications
16
320
4
1
Order By: Relevance
“…Nevertheless, the dorsoanterior development, craniofacial patterning, and marker expression in the embryos and of the resulting larvae were normal, revealing that this effect is not inducing major alterations of head or heart morphogenesis (as would be expected if large numbers of cells were diverted from other neural crest lineages or if major and nonspecific changes in signaling factor expression were being caused). These data reveal that KCNE1 misexpression induces ectopic expression of powerful regulators of both neural crest and neoplastic cell behavior (35)(36)(37)(38).…”
Section: Kcne1 Induces Neural Crest/tumor Regulator Gene Expression In Amentioning
confidence: 87%
“…Nevertheless, the dorsoanterior development, craniofacial patterning, and marker expression in the embryos and of the resulting larvae were normal, revealing that this effect is not inducing major alterations of head or heart morphogenesis (as would be expected if large numbers of cells were diverted from other neural crest lineages or if major and nonspecific changes in signaling factor expression were being caused). These data reveal that KCNE1 misexpression induces ectopic expression of powerful regulators of both neural crest and neoplastic cell behavior (35)(36)(37)(38).…”
Section: Kcne1 Induces Neural Crest/tumor Regulator Gene Expression In Amentioning
confidence: 87%
“…The tumor invasion and metastasis are initiated by EMT program involving cells acquiring mesenchymal phenotype characterized with decreased cell‐to‐cell adhesion, increased motility and invasive properties. Such cells once detached from primary tumor invade surrounding tissues through collective or individual cell migration 3, 20, 21, 22, 23, 24, 25, 26, 67, 68, 69, 70, 71, 73. Therefore, we propose that fibroblasts infected with H. pylori (cagA+vacA+) likely acquired characteristics of CAFs with changes in morphology and elevated HGF, TGFβ, and additionally IL‐6 and SDF‐1 release, which may enhance EMT program in epithelial gastric cells.…”
Section: Discussionmentioning
confidence: 99%
“…These events are facilitated by the reduction in cell‐cell adhesion molecule E‐cadherin, the upregulation of more plastic mesenchymal proteins such as vimentin, N‐cadherin, and α‐SMA and deregulation of the Wnt pathway 23, 24. Many EMT‐inducing transcription factors (EMT‐TFs) such as Twist1, Snail1, Snail2, Zeb1, and Zeb2 can repress E‐cadherin both directly or indirectly 23, 24, 25, 26…”
Section: Introductionmentioning
confidence: 99%
“…Snail can down-regulate expression of E-cadherin, inducing EMT and promoting cell migration and invasion [22,44] . Overexpression of Snail was detected in various tumor cell lines, including breast, pancreatic and gastric cancers [45][46][47] . It was recently reported that Akt could up-regulate Snail expression and induce invasion [40,48] .…”
Section: Discussionmentioning
confidence: 99%